Answer:
The answer is (x + 3) (x - 7) = 0
Step-by-step explanation:
x² - 4x = 21
x² - 4x - 21 = 0
x² - 7x + 3x - 21 = 0
x(x - 7) + 3(x - 7) = 0
(x + 3) (x - 7) = 0
Thus, The answer is (x + 3) (x - 7) = 0
<em><u>-TheUnknownScientist</u></em>
Answer:
the value is 36
Step-by-step explanation: so you add
2(2)+3y=13
4+3y=13
3y=9
y=3
The answer is B
All three numbers multiplied to get the volume
surface area is the formula times base 1 and base 2 times base 3 and answer
Answer:
A)
Step-by-step explanation:
For f, x would equal 0. 0/2 would equal 2 since it has no value.
Hope this helps!
<em>-kiniwih426</em>